2007
DOI: 10.2337/dc06-2131
|View full text |Cite
|
Sign up to set email alerts
|

Masked Hypertension, Urinary Albumin Excretion Rate, and Echocardiographic Parameters in Putatively Normotensive Type 2 Diabetic Patients

Abstract: OBJECTIVE -To evaluate the impact of masked hypertension in normotensive type 2 diabetic patients on microvascular complications and echocardiographic parameters. RESEARCH DESIGN AND METHODS-A cross-sectional study was conducted in 135 normotensive patients with type 2 diabetes. Patients underwent urinary albumin excretion rate (UAER) measurement, echocardiography, and 24-h ambulatory blood pressure monitoring (ABPM). Patients with increased daytime blood pressure levels (Ն135/85 mmHg) were classified as havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 23 publications
8
55
2
1
Order By: Relevance
“…Prevalence of masked hypertension in series evaluating normotensive patients with diabetes was 25-50% [19][20][21][22] or 440% in diabetic hypertensives showing adequate control of BP. 23 These studies have shown that masked hypertension conferred unfavorable outcomes, thus evaluation of ambulatory BP may be indicated in normotensive diabetic patients 21 and in hypertensive cases with controlled office BP.…”
Section: Discussionmentioning
confidence: 95%
“…Prevalence of masked hypertension in series evaluating normotensive patients with diabetes was 25-50% [19][20][21][22] or 440% in diabetic hypertensives showing adequate control of BP. 23 These studies have shown that masked hypertension conferred unfavorable outcomes, thus evaluation of ambulatory BP may be indicated in normotensive diabetic patients 21 and in hypertensive cases with controlled office BP.…”
Section: Discussionmentioning
confidence: 95%
“…Despite this, in previous investigations of the prevalence of masked hypertension in diabetes, the definition of masked hypertension has been restricted to out-of-clinic BP values obtained during the awake part of the day, using either self-measured BP [1,2] or ambulatory BP [3,4,13]. We report for the first time the prevalence of MNHT in type 2 diabetes, and conclude that it is more common than masked day-time hypertension and identifies more accurately the patients at elevated risk for macrovascular complications of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In type 2 diabetes, masked hypertension-defined as normal blood pressure when measured in the clinic but elevated BP when measured out of the clinic during the awake part of the day-is associated with an increased prevalence of retinopathy, nephropathy and coronary heart disease [1] and with target organ damage [2][3][4]. However, it is not known whether masked nocturnal hypertension (MNHT)-defined as normal BP when measured in the clinic but elevated BP when measured away from the clinic during the night-is a more useful tool for the identification of patients at high risk than masked hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…1 Patients with MH may have exaggerated BP response to ordinary daily stressors, with physical exercise being one possible trigger. The results of this cross-sectional study showed that type II diabetic patients with MH have an exaggerated BP response to exercise, which may confer an increased cardiovascular risk.…”
mentioning
confidence: 99%
“…1,2 MH has been observed in 30% of office normotensive type II DM patients and is associated with higher urinary albumin excretion rate and increased left ventricular mass in comparison with patients with normal BP levels at both the office and ABPM. 1 Patients with MH may have exaggerated BP response to ordinary daily stressors, with physical exercise being one possible trigger. Therefore, the aim of this study was to evaluate the response of BP during exercise in normotensive and MH type II DM patients.…”
mentioning
confidence: 99%